2009
DOI: 10.1179/ssa.2009.3.3.265
|View full text |Cite
|
Sign up to set email alerts
|

Motivational Factors Influencing Sport Spectator Involvement At NCAA Division II Basketball Games

Abstract: The purpose of this study was to investigate the motivational factors affecting sport spectator involvement using 304 spectators from NCAA Division II men's and women's basketball games. Two aspects (behavioral and socio-psychological) of sport spectator involvement were examined. The results revealed that spectators at intercollegiate basketball games had a higher level of socio-psychological involvement than behavioral involvement. A series of multiple regression analyses were conducted to examine the affect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(8 citation statements)
references
References 17 publications
(9 reference statements)
0
8
0
Order By: Relevance
“…Fan identification, involvement opportunity, and reference groups were established as influential factors that had a significant impact on overall sports fans' involvement (Martin et al, 2009). Also, the results and the outcome from the interview was divided into questions about fan involvement, public relations, management, cultural issues, marketing efforts, and cooperation with sponsors.…”
Section: Discussionmentioning
confidence: 99%
“…Fan identification, involvement opportunity, and reference groups were established as influential factors that had a significant impact on overall sports fans' involvement (Martin et al, 2009). Also, the results and the outcome from the interview was divided into questions about fan involvement, public relations, management, cultural issues, marketing efforts, and cooperation with sponsors.…”
Section: Discussionmentioning
confidence: 99%
“…Studies on loyalty mentioned that satisfaction with club games has been referred to as an antecedent of the spectators, behavioural intentions and their emotions experienced during the matches, service quality, team brand associations, commitment, brand identification, perceived value, customer relationship, trust, customer retention, waiting time and dependability are loyalty consumption-related aspects often mentioned as having a direct or indirect role (i.e. via satisfaction) in increasing spectators' behavioural intentions (Abeza, O'Reilly & Reid 2013:120;Baker & Jones 2011:52;Biscaia et al 2013:14-25, 20-32;Choi et al 2009 Kim & Trail 2010:192;Kruger et al 2010:91-92;Yoshida & James 2010:338) has identified several factors such as prizes, inclement and deterrent weather before and during the event, lack of resources and access, time conflict between the professional tournament and everyday life activities, inconvenience, lengthy distance to travel to the event, poor player performance, seating and difficulty in finding parking as constraints and challenges faced by managers that impact on spectator attendance at the games.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some authors, such as Choi, Martin, Park and Yoh (2009) have divided such motives into two categories, being psycho-sociological (personal or individual) and behavioural (game) related factors. From this perspective, personal or individual factors were associated with motives of vicarious achievement, aesthetics, the experience of drama or eustress and escape from daily life problems.…”
Section: Motivation For Sport Consumptionmentioning
confidence: 99%
“…Similarly, game-related motivational factors related to the spectator's acquisition of game-related knowledge, the appreciation of the physical skill of the athletes, the physical attractiveness of players and the social interaction amongst spectators. The differentiation between personal or individual and gamerelated consumption factors provide a structured means through which to understand the psychological attachment of spectators to the sport (Baller, 2015;Choi et al, 2009). As a collective, these factors primarily influence the decision of the spectator to consume sport and are directly related to buying behaviours (Cottingham et al, 2014;Izzo et al, 2014).…”
Section: Motivation For Sport Consumptionmentioning
confidence: 99%